Технологічні аспекти створення пульсаційного гомогенізатора для диспергування молочної сировини - Паляничка, Надія Олександрівна; Palianychka, Nadiia; Ковальов, Олександр Олександрович; Kovalov, Oleksandr; Червоткіна, Олександра Олександрівна; Chervotkina, Oleksandra; Прокопенко, Олена Павлівна; Prokopenko, Olena (Запоріжжя: ТДАТУ, 2025)
UA: У роботі проаналізовано ключові технологічні особливості розроблення пульсаційного гомо-генізатора, який застосовується у процесі диспергування молочної сировини. Гомогенізація, що забезпечує диспергування, є одним із провідних етапів технологічної лінії переробки молока та виготовлення молочної продукції. Саме якість виконання цього процесу визначає смакові властивості та споживчі характеристики кінцевого продукту. Разом із тим дослідження довели, що традиційні гомогенізатори відзначаються значни-ми енерговитратами, що робить даний процес одним із найбільш енергоємних у виробництві. Для зниження цих витрат пропонується впровадження нового типу обладнання – пульсаційних гомогенізаторів, здатних забезпечити необхідну якість продукції за істотного зменшення споживання електроенергії. У статті наве-дено розрахунки основних режимів роботи та параметрів таких апаратів, а також визначено вимоги до їх конструкторських рішень. /// EN: One of the most common technological processes is the dispersion of emulsions by homogenization in specialized equipment. This method is used in the agricultural sector, food, chemical, processing and a number of other industries. In food production, homogenization is widely used for the production of milk and dairy products, ice cream mixes, condensed milk, mayonnaise, ketchup, margarine, egg melanges, juices and various food products. At the same time, this process has become most widespread in the dairy industry. The use of homogenization in the production of drinking milk allows you to significantly improve its organoleptic characteristics, ensure better stability and viscosity, avoid fat deposition on the walls of the equipment and increase digestibility by reducing the size of fat globules. Modern equipment, which is widely used in enterprises, provides a high level of homogenization, but is characterized by significant energy costs. The main technical difficulty in obtaining fine emulsions is the limited capabilities of such devices. That is why the development of new methods and equipment for the formation of fine emulsions, which allow you to adjust the degree of dispersion while maintaining high productivity, is becoming particularly relevant. Previous studies have allowed us to identify a new promising type of equipment – a pulsating homogenizer. The paper presents the results of calculations of the main parameters and modes of its operation and defines the requirements for its design. The analysis showed that the pulsating milk homogenizer is characterized by the following parameters: productivity – 1800 kg/h, maximum pressure – 1.5 MPa, working chamber length – 0.5 m, working chamber diameter – 0.3 m at an installed power of 2 kW. If necessary, these parameters can be adjusted based on the calculations, which allows you to adapt the installation to the capacity of a specific production enterprise.
Technological aspects of creating a pulse homogenizer for dispersing milk raw material
Keywords: диспергування; конструкція; пульсаційний гомогенізатор; енерговитрати; технологічна лінія; параметри; dispersion; design; pulsating homogenizer; energy consumption; technological line; parameters; product; quality; energy consumption; dairy products